PENERAPAN MODEL MULTILITERASI BERBASIS MEDIA CANVA DALAM PEMBELAJARAN MENULIS TEKS PROSEDUR PADA SISWA KELAS VII SMPN 1 SLIYEG TAHUN AJARAN 2024/2025 - Tri Yanah; Muhammad Sholeh; Muji Zain Naufal (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research was motivated by variations in learning that were less interesting so that students experienced difficulty in determining linguistic rules in the form of procedural texts. Thus, the aims of this research are: 1) to find out whether the application of the multiliteracy model based on Canva media in learning to write procedural texts for class VII students at SMPN 1 Sliyeg for the 2024/2025 academic year is effective; 2) to describe how the learning activity is to write procedural texts by applying the multiliteracy model based on Canva media for class VII students at SMPN 1 Sliyeg for the 2024/2025 academic year. The research method used in this research is an experimental study. The method for collecting data in this research is by collecting data from observations and tests (pretest and posttest). Based on the results of statistical calculations using the independent samples t-test, it was obtained that tcount was 3.919 and ttable was 1.672, which shows that H0 was rejected and H1 was accepted. This explains that the influence of using the Canva media-based multiliteracy model in the experimental class can produce a more effective impact compared to the PowerPoint-based cooperative learning model applied in the control class. Based on the results of observations made, it is proven that the application of the multiliteracy model based on Canva media can increase student activity in learning to write procedural texts in class VII SMPN 1 Sliyeg.